IMPROVEMENT OF ORTHOPEDIC CARE FOR MILITARY PERSONAL DURING WARTIME - N.V. Tsvetkova; O.A. Pisarenko; V.M. Sokolovska; M.Ya. Nidzelskyi (Український стоматологічний альманах)
In the current situation of Russian military aggression against Ukraine, the dental health of military personnel is a key concern. Poor dental health impacts the overall well-being of the military, which in turn affects combat tasks and quality of life. Various studies show that 90% of military personnel require dental care.